Heat and salinity budgets at the Stratus mooring in the southeast Pacific. Issue 11 (28th November 2014) - Holte, James; Straneo, Fiammetta; Farrar, J. Thomas; Weller, Robert A.
Abstract The surface layer of the southeast Pacific Ocean (SEP) requires an input of cold, fresh water to balance heat gain, and evaporation from air‐sea fluxes. Models typically fail to reproduce the cool sea surface temperatures (SST) of the SEP, limiting our ability to understand the variability of this climatically important region. We estimate the annual heat budget of the SEP for the period 2004–2009, using data from the upper 250 m of the Stratus mooring, located at 85°W 20°S, and from Argo floats. The surface buoy measures meteorological conditions and air‐sea fluxes; the mooring line is heavily instrumented, measuring temperature, salinity, and velocity at more than 15 depth levels. We use a new method for estimating the advective component of the heat budget that combines Argo profiles and mooring velocity data, allowing us to calculate monthly profiles of heat advection. Averaged over the 6 year study period, we estimate a cooling advective heat flux of −41 ± 29 W m−2, accomplished by a combination of the mean gyre circulation, Ekman transport, and eddies. This compensates for warming fluxes of 32 ± 4 W m−2 due to air‐sea fluxes and 7 ± 9 W m−2 due to vertical mixing and Ekman pumping. A salinity budget exhibits a similar balance, with advection of freshwater (−60 psu m) replenishing the freshwater lost through evaporation (47 psu m) and Ekman pumping (14 psu m).